Development of a Network DEA Model to Measure Production Line’s Performance: A Conceptual Paper - N. A. M. A., Zainal; Muhamad Arifpin, Mansor; S. N., M. Saffe (2016)
Production line in manufacturing industry usually is made up of several processes and must go through performance measurement to determine whether they are efficient or inefficient. The extended DEA model which is the Network DEA is developed to look inside the DMU and find the source of inefficiency of each sub DMUs. Our goals of developing the Network DEA model on the production line are to identify the inputs and outputs required and to consider the relationship and connection between each of the processes in the production line and thus measure the performance of the entire production line. The expected outcome of this paper is to propose a conceptual model that can be used for performance measurement in manufacturing production line.